CRIP1 expression in monocytes related to hypertension. Issue 7 (16th April 2021) - Schweigert, Olga; Adler, Julia; Längst, Natalie; Aïssi, Dylan; Duque Escobar, Jorge; Tong, Teng; Müller, Christian; Trégouët, David-Alexandre; Lukowski, Robert; Zeller, Tanja
Abstract: Hypertension is a complex and multifactorial disorder caused by lifestyle and environmental factors, inflammation and disease-related genetic factors and is a risk factor for stroke, ischemic heart disease and renal failure. Although circulating monocytes and tissue macrophages contribute to the pathogenesis of hypertension, the underlying mechanisms are poorly understood. Cysteine rich protein 1 (CRIP1) is highly expressed in immune cells, and CRIP1 mRNA expression in monocytes associates with blood pressure (BP) and is up-regulated by proinflammatory modulation suggesting a link between CRIP1 and BP regulation through the immune system. To address this functional link, we studied CRIP1 expression in immune cells in relation to BP using a human cohort study and hypertensive mouse models. CRIP1 expression in splenic monocytes/macrophages and in circulating monocytes was significantly affected by angiotensin II (Ang II) in a BP-elevating dose (2 mg/kg/day). In the human cohort study, monocytic CRIP1 expression levels were associated with elevated BP, whereas upon differentiation of monocytes to macrophages this association along with the CRIP1 expression level was diminished. In conclusion, CRIP1-positive circulating and splenic monocytes seem to play an important role in hypertension related inflammatory processes through endogenous hormones such as Ang II. These findings suggest that CRIP1 may affect the interaction between the immune system, in particular monocytes, and the pathogenesis of hypertension.